1990
DOI: 10.1364/ao.29.003213
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric transmission spectroscopy using the sun as the source

Abstract: A method is presented to obtain normalized high resolution slant path transmittance spectra of the atmosphere. Sample spectra are presented. The spectra are of use in remote sensing applications for various types of atmospheric physics and atmospheric photochemistry research, for validating line parameter compilations, and for modeling slant path radiative transfer. The sample spectra are used to demonstrate improved accuracy of line-by-line transmission models when recently reported water vapor line parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…While the spectroscopic parameters for O 2 have been trusted by the community for many years, recent studies 2,3,4 have suggested that the quoted values for the near-infrared water lines need to be reconsidered. Historically, water vapor spectral measurements in the near-IR region just beyond 1000 nm are sparse owing to the lack of good light sources and detectors at those wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…While the spectroscopic parameters for O 2 have been trusted by the community for many years, recent studies 2,3,4 have suggested that the quoted values for the near-infrared water lines need to be reconsidered. Historically, water vapor spectral measurements in the near-IR region just beyond 1000 nm are sparse owing to the lack of good light sources and detectors at those wavelengths.…”
Section: Introductionmentioning
confidence: 99%